Genomic characterization and population structure of indigenous cavies from the Democratic Republic of Congo: Implications for breeding and conservation - Ayagirwe, R.; Kyallo, Martina; Meutchieye, F.; Manjeli, Y.; Mutwedu, V.B.; Mugumaarhahama, Y.; Baenyi, P.; Wasso, S.; Bisimwa, P.; Yao, Nasser (Elsevier, 2025)
Domesticated guinea pigs (cavies) are crucial in mixed crop-livestock farming systems in the Democratic Republic of the Congo (DRC), providing meat, income, and organic fertilizer. This research assessed the genetic diversity and population structure of guinea pig populations from South Kivu, North Kivu, Katanga, and Kinshasa. A total of 343 samples were screened using thirteen (13) polymorphic simple sequence repeat (SSR) markers. The study identified 113 alleles across the four populations, with an average of 5.77 alleles per locus per population. South Kivu had the highest allele count (7.23), while Kinshasa had the lowest (4.69). The mean observed heterozygosity (Ho) and expected heterozygosity (He) were 0.34 and 0.58, respectively. Genetic analysis showed higher levels of inbreeding (FST=0.080, FIS=0.464) with observed heterozygosity (50.7%) lower than expected. Genetic diversity within populations was lower compared to between populations. South Kivu exhibited the lowest inbreeding rate among other African populations. The observed molecular variance suggests potential for selection within populations before crossbreeding, providing avenues for genetic enhancement. Phylogenetic analysis of the 343 individuals grouped them into three distinct clusters, indicating that DRC’s cavy populations consist of three gene pools. This study on guinea pigs’ molecular diversity offers valuable insights for breeding programs, facilitating the selection of genetically diverse parents to establish breeding populations aimed at improving and conserving guinea pigs.